"Doping" pentacene with sp2-phosphorus atoms: towards high performance ambipolar semiconductors. Issue 4 (8th January 2016) - Long, Guankui; Yang, Xuan; Chen, Wangqiao; Zhang, Mingtao; Zhao, Yang; Chen, Yongsheng; Zhang, Qichun
Abstract : "Doping" pentacene with sp 2 -phosphorus atoms could efficiently decrease both the hole and electron reorganization energies. Abstract : Recent research progress in black phosphorus sheets strongly encourages us to employ pentacene as a parent system to systematically investigate how the "doping" of sp 2 -phosphorus atoms onto the backbone of pentacene influences its optical and charge transport properties. Our theoretical investigations proved that increasing the contribution of the p z atomic orbital of the sp 2 -phosphorus to the frontier molecular orbital of phosphapentacenes could significantly decrease both hole and electron reorganization energies and dramatically red-shift the absorption of pentacene. The record smallest hole and electron reorganization energies of 69.80 and 95.74 meV for heteropentacene derivatives were obtained. These results suggest that phosphapentacenes (or phosphaacenes) could be potential promising candidates to achieve both higher and balanced mobilities in organic field effect transistors and realize a better power conversion efficiency in organic photovoltaics.